Ten-year survival after High-Dose-Rate Brachytherapy combined with External Beam Radiation Therapy in high-risk prostate cancer: A comparison with the Norwegian SPCG-7 cohort. (March 2019) - Wedde, Trude B.; Småstuen, Milada C.; Brabrand, Sigmund; Fosså, Sophie D.; Kaasa, Stein; Tafjord, Gunnar; Russnes, Kjell M.; Hellebust, Taran P.; Lilleby, Wolfgang
Highlights: Observational study of 10-year survival in high-risk Prostate Cancer (PCa) after High-Dose-Rate brachytherapy combined with External Beam Radiation Therapy (HDR-BT/EBRT) compared to EBRT alone. The combined HDR-BT/EBRT treatment was found to give a 3.6-fold decrease in Prostate Cancer Specific Mortality (PCSM) and a 1.6-fold decrease in Overall Mortality (OM). Gleason score and type of treatment strongly influenced PCSM whereas only treatment modality was associated with OM. The observed benefits of dose-escalation warrant future randomized trials. Abstract: Background: The survival benefit of dose-escalation with High-Dose-Rate brachytherapy (HDR-BT) boost combined with External Beam Radiotherapy (EBRT) for the treatment of high-risk prostate cancer (PCa) remains debatable. We investigated 10-year PCa-specific mortality (PCSM) and overall mortality (OM) in high-risk patients treated with HDR-BT/EBRT (calculated EQD2 = 102 Gy) compared to EBRT alone (70 Gy). Methods: HDR-BT boosts (10 Gy × 2) were given 2 weeks apart followed by 50 Gy conformal EBRT (2 Gy × 25) to the prostate and seminal vesicles. The HDR-BT/EBRT group (N:325) received Androgen Deprivation Therapy for a median duration of 2 years. The historical control group (N:296), received a median dose of 70 Gy (2 Gy × 35) to the prostate and seminal vesicles with lifelong Anti-Androgen Treatment. For each treatment group PCSM and OM were established by competing-risk analyses and Kaplan–Meier analyses respectively. Differences were evaluated by the logrank test. Independent associations were established by Cox regression analyses. Significance level set to p < 0.05. Results: Median follow-up was 104 and 120 months for the HDR-BT/EBRT and the EBRT group respectively. A 3.6-fold decreased risk of PCSM ( p < 0.01) and a 1.6-fold decreased risk of OM ( p = 0.02) in the HDR-BT/EBRT cohort compared to the EBRT-only group were revealed. Ten-year OM and PCSM rates were 16% and 2.5% in the HDR-BT/EBRT group versus 23% and 8.2% in the EBRT-only group respectively. Both treatment modality (HR = 3.59, 95%CI 1.50–8.59) and Gleason score (HR = 2.48, 95%CI 1.18–5.21) were associated with PCSM. Only treatment modality (HR = 1.63, 95%CI = 1.08–2.44) was significantly associated with OM. Conclusions: Men with high-risk PCa have a significantly reduced PCSM and OM rates when treated with dose-escalated radiotherapy achieved by HDR-BT/EBRT compared to EBRT alone (70 Gy). A Gleason score of 8–10 was independently associated with increased risk of PCSM. Randomized studies are warranted. Summary: Observational study of 10-year survival in high-risk Prostate Cancer (PCa) after High-Dose-Rate brachytherapy combined with External Beam Radiation Therapy (HDR-BT/EBRT) compared to EBRT alone. The combined HDR-BT/EBRT treatment was found to give a 3.6-fold decrease in Prostate Cancer Specific Mortality (PCSM) and a 1.6-fold decrease in Overall Mortality (OM). Gleason score and type of treatment strongly influenced PCSM whereas only treatment modality was associated with OM. The observed benefits of dose-escalation warrant future randomized trials.